CURRENT ACCOUNT SHOCKS AND RUPIAH EXCHANGE RATE DYNAMICS: A VAR ANALYSIS AMID MACROECONOMIC FLUCTUATIONS - Eka Dini Rahmawati; Dini Yuniarti (JAT : Journal Of Accounting and Tax, 2026)
The purpose of this research is to examine the impact of current account balance, GDP growth, inflation, and interest rates on the dynamics of the rupiah exchange rate in Indonesia. This study examines two major exchange rate regimes (managed floating and freely floating exchange rates) using annual time-series data from 1985 to 2024 to analyze structural and cross-policy changes in economic policy. Vector Error Correction Model (VECM) methodology is the analytical framework employed to identify both short-term dynamics and long-term equilibrium relationships. The test outcomes demonstrates that there is a long-term structural linkage that is interconnected. In the long term, the current account balance, GDP growth, inflation, and interest rates are proven to contribute to exchange rate dynamics, which at the same time supports the relevance of the External Balance, Balassa-Samuelson, PPP, and IRP theories in Indonesia. In contrast, in the short term, the influence of these macroeconomic variables is relatively limited. The results of the IRF and FEVD confirm that the short-term fluctuations of the rupiah are more dominated by internal exchange rate shocks themselves. Overall, the PPP mechanism is considered more relevant in explaining the volatility of the rupiah in Indonesia than the IRP mechanism on the short term. The policy recommendations emphasize the importance of coordination between Bank Indonesia and the government in controlling inflation and reducing the current account deficit in order to maintain exchange rate stability in a sustainable manner.